PROX1 Gene Variant is Associated with Fasting Glucose Change After Antihypertensive Treatment. Issue 2 (9th October 2013) - Gong, Yan; McDonough, Caitrin W.; Beitelshees, Amber L.; Karnes, Jason H.; O'Connell, Jeffrey R.; Turner, Stephen T.; Chapman, Arlene B.; Gums, John G.; Bailey, Kent R.; Boerwinkle, Eric; Johnson, Julie A.; Cooper‐DeHoff, Rhonda M.
<x xml:space="preserve">Abstract</x> Study Objective To assess the relationship of the 33 single nucleotide polymorphisms (SNPs) previously associated with fasting glucose in Caucasians in genome‐wide association studies (GWAS) with glucose response to antihypertensive drugs shown to increase risk for hyperglycemia and diabetes. Design Randomized, multicenter clinical trial. Patients A total of 456 Caucasian men and women with uncomplicated hypertension. Measurements and Main Results The Pharmacogenomic Evaluation of Antihypertensives Responses study evaluated blood pressure and glucose response in uncomplicated hypertensive patients randomized to either atenolol or hydrochlorothiazide (HCTZ) monotherapy, followed by combination therapy with both agents. Association of these SNPs with atenolol‐ or HCTZ‐induced glucose response was evaluated in 456 Caucasian patients using linear regression adjusting for age, sex, body mass index, baseline glucose, baseline insulin, and principal component for ancestry. The SNP rs340874 in the 5′ region of PROX1 gene was significantly associated with atenolol‐induced glucose change (p=0.0013). Participants harboring the C allele of this SNP had greater glucose elevation after approximately 9 weeks of atenolol monotherapy (β = +2.39 mg/dl per C allele), consistent with the direction of effect in fasting glucose GWAS, that showed the C allele is associated with higher fasting glucose. Conclusion These data suggest that PROX1 SNP rs340874, discovered in fasting glucose GWAS, may also be a pharmacogenetic risk factor for antihypertensive‐induced hyperglycemia. β‐blockers and thiazides may interact with genetic risk factors to increase risk for dysglycemia and diabetes.